Round-Robin test of split Hopkinson pressure bar. (April 2019) - Kariem, Muhammad A.; Santiago, Rafael C.; Govender, Reuben; Shu, Dong Wei; Ruan, Dong; Nurick, Gerald; Alves, Marcilio; Lu, Guoxing; Langdon, Genevieve S.
Highlights: Round-robin has been conducted at four universities with different apparatus, setting and data processing. Compressive SHPB tests have been conducted on four metals: commercially pure copper, stainless steel grade 316, aluminium 1100 and magnesium alloy This research shows comparable results in terms of true stress – true strain and final true strain at similar true strain rates. The result indicates the possibility of SHPB standardization in the near future. Abstract: A Round-Robin test using split Hopkinson pressure bars (SHPBs) has been conducted by four universities: Swinburne University of Technology (SUT), Australia; University of São Paulo (USP), Brazil; University of Cape Town (UCT), South Africa; and Nanyang Technological University (NTU), Singapore. Each university had different sets of SHPBs and data acquisition systems. The bars were made of maraging 350 (SUT), SAE 1055 (USP), stainless steel 17–4 pH (UCT), and stainless steel 304 (NTU), respectively. The bar diameters were in a range of 12.7 to 24.99 mm and the lengths of the pressure bars were from 700 mm to 2000 mm. Compressive SHPB tests have been conducted on four metals: commercially pure copper, stainless steel grade 316 (SS316), aluminium alloy 1100 and magnesium alloy. The strain signals and stress-strain curves for each material measured by four universities have been compared and discussed. The results showed that the flow stress fluctuated in a range of ± 9.9% for copper,  ± 3.3% for SS316,  ± 6.7% for aluminium and ± 15.6% for magnesium. Specific strain rate or final true strains were not targeted in this study. Hence the strain rates ranged from 987 to 2690 s −1, and final true strains varied from 0.12 to 0.38. This international collaboration attempts to provide evidence for the possible standardization of SHPB tests in the future.